2015
DOI: 10.2174/138955751503150312141854
|View full text |Cite
|
Sign up to set email alerts
|

In-silico Analyses of Natural Products on Leishmania Enzyme Targets

Abstract: Natural products are compounds that are isolated from plants, provide a variety of lead structures for the development of new drugs by the pharmaceutical industry. The interest in these substances increases because of their beneficial effects on human health, which include antiviral, antiallergic, antiplatelet, anti-inflammatory, antitumor, antioxidant, and antiparasitic activities. Leishmaniasis is the infection caused by protozoa of the genus Leishmania, which affects mainly people who live in poor countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 53 publications
0
22
0
2
Order By: Relevance
“…The "in-silico" analysis which stands for computer-based biological experiments, is a state-of-the-art and accurate method to discover exclusive bioactive compounds, which may represent novel metabolic pathways and/or a powerful affinity to a certain target (42). In this sense, several studies have identified unprecedented molecules for various drug targets in Leishmania, such as pteridine reductase1, tryparedoxin peroxidase and sterol biosynthesis (43)(44)(45)(46)(47)(48), as well as in other single-celled eukaryotes enclosing Toxoplasma gondii, Cryptosporidium hominis, Plasmodium and Trypanosoma cruzi (49)(50)(51). Current in-silico investigation was aimed to screen and predict the anti-leishmanial potency of 3358 FDA-approved compounds against both drug targets in L. infantum in comparison to amphotericin B and glucantime for the discovery of new biochemical molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The "in-silico" analysis which stands for computer-based biological experiments, is a state-of-the-art and accurate method to discover exclusive bioactive compounds, which may represent novel metabolic pathways and/or a powerful affinity to a certain target (42). In this sense, several studies have identified unprecedented molecules for various drug targets in Leishmania, such as pteridine reductase1, tryparedoxin peroxidase and sterol biosynthesis (43)(44)(45)(46)(47)(48), as well as in other single-celled eukaryotes enclosing Toxoplasma gondii, Cryptosporidium hominis, Plasmodium and Trypanosoma cruzi (49)(50)(51). Current in-silico investigation was aimed to screen and predict the anti-leishmanial potency of 3358 FDA-approved compounds against both drug targets in L. infantum in comparison to amphotericin B and glucantime for the discovery of new biochemical molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In Trypanosoma cruzi , (–)-epicatechin has been described to affect the arginine kinase activity and NADH-oxidase activity (Paveto et al, 2004 ; Maya et al, 2007 ; Scotti et al, 2010 ; Dodson et al, 2011 ). In Leishmania donovani , it was reported that kaempferol promotes the inhibition of the activity of pyruvate kinase, the dihydroorotase enzyme (LdDHOase) and the cytidine deaminase, which impact the pyrimidine biosynthesis pathway, causing the death of the parasites (Scotti et al, 2015 ; Tiwari et al, 2016 ). In the case of Toxoplasma gondii , quercetin inhibits the synthesis of HSP90, HSP70, and HSP27, that have been described as virulence factors (Dobbin et al, 2002 ; Kerboeuf et al, 2008 ).…”
Section: Flavonoids and Their Molecular Targets In Protozoamentioning
confidence: 99%
“…Adenosine kinase is one of the enzymes in the purine salvage pathway, and Leishmania adenosine kinase is crucial for parasite survival [404]. Molecular docking (Glide, FlexX, GOLD) of a library of An in-silico analysis of a dataset of 683 flavonoids for molecular docking to L. mexicana pyruvate kinase found that 3-glycosylated flavonoids (seven compounds), 6,8-diglycosyl flavonoids (one compound), and biflavonoids (four compounds) were the most promising ligands [400]. Promastigote surface antigen has been identified as a common protein drug target for L. braziliensis, L. major, and L. infantum.…”
Section: Leishmania and Trypanosoma Targetsmentioning
confidence: 99%
“…Herrmann and co-workers have carried out an in-silico screening of a natural products library of 700 structures against T. brucei glyceraldehyde-3-phosphate dehydrogenase (TbGAPDH) [399]. These investigators were able to identify 13 "hits" based on the molecular docking and of these, five compounds (three geranylated benzophenones, flavaspidic acid AB, and a bis-resorcinyl tetradecene derivative, Figure 11) An in-silico analysis of a dataset of 683 flavonoids for molecular docking to L. mexicana pyruvate kinase found that 3-glycosylated flavonoids (seven compounds), 6,8-diglycosyl flavonoids (one compound), and biflavonoids (four compounds) were the most promising ligands [400]. Promastigote surface antigen has been identified as a common protein drug target for L. braziliensis, L. major, and L. infantum.…”
Section: Leishmania and Trypanosoma Targetsmentioning
confidence: 99%